Symbols of Femininity in Arabic Grammatical Studies - Satni Satni; Moch. Mu'izzuddin; Hannanah Mukhtar Thabrani; Aspandi Aspandi (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This study aims to provide an overview and examine the concept of muannats in Arabic grammatical studies. The method used for this research is the library research method, with primary data sources in the form of classical books and secondary data sources in the form of journals, books, and articles related to the titles. From the research results, it is found that muannats has a sign to show its femininity in both isim and fi'il. Muannats, according to its authenticity, is divided into two, namely muannats haqiqi and muannats ghair haqiqi. The sign of ta'nits that appears most often is taâ€™; ta' itself has many functions besides gender distinction. Muannats in general has fifteen signs; in isim, there are eight signs fiâ€™il there are four signs, and object, there are three signs. Finally, there are two alifs that function as a sign of muannats, namely alif maqshurah and alif mamdudah. The ta'nits marked by alif ta'nits maqshurah can follow the wazan ÙÙØ¹Ù’Ù„ÙŽÙ‰ while the sign of alif ta'nits mamdudah follows the wazan